Early Hebrew education and its significance for present-day educational theory and practice - Schoeman, S. (Hervormde teologiese studies, 1997)
Early Hebrew education and its significance for present-day educational theory and practice The history of education in antiquity is not without relevance to present-day educational theory and practice. The focus in this article is on the early Hebrews and their education. A study of early Hebrew education may in itself not provide solutions to current educational problems, but it may be useful in offering new perspectives, encouragement and suggestions for a juture South African educational dispensation.